2019
DOI: 10.1002/jcb.28620
|View full text |Cite
|
Sign up to set email alerts
|

The expression profiling of circulating miR‐204, miR‐182, and lncRNA H19 as novel potential biomarkers for the progression of peptic ulcer to gastric cancer

Abstract: Deregulation of noncoding RNAs, microRNAs (miRNAs) and long noncoding RNA (lncRNA), are implicated in the initiation and progression of gastric cancer (GC). This study is a pilot case‐control study carried out on 75 subjects, 40 of them were Helicobacter pylori‐gastric ulcer patients and 35 were GC patients recruited from the Gastrointestinal Endoscopy Unit in Al‐Kasr Al‐Aini Hospital, Cairo University in Egypt. Real‐time PCR was performed to evaluate the expression level of serum miR‐204, miR‐182, and lncRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…The serum levels of lncRNA H19, together with miR-204, miR-182 were recently proposed as prospective plasma biomarkers to detect GC and its progression from ulcer caused by H. pylori . The authors indeed showed that serum lncRNA H19 has a high diagnostic accuracy, specificity and sensitivity [146]. Another work, on bladder cancer (BC), showed a positive correlation among serum exosomal H19 with total H19 level in paired cancer tissues.…”
Section: Lncrnas Diagnostic Prognostic and Therapeutic Perspectivesmentioning
confidence: 99%
“…The serum levels of lncRNA H19, together with miR-204, miR-182 were recently proposed as prospective plasma biomarkers to detect GC and its progression from ulcer caused by H. pylori . The authors indeed showed that serum lncRNA H19 has a high diagnostic accuracy, specificity and sensitivity [146]. Another work, on bladder cancer (BC), showed a positive correlation among serum exosomal H19 with total H19 level in paired cancer tissues.…”
Section: Lncrnas Diagnostic Prognostic and Therapeutic Perspectivesmentioning
confidence: 99%
“…Based on TCGA data, integrating expression analysis and survival analysis of these lncRNAs, only 1 lncRNA (H19) was considered as the central lncRNA. Moreover, overexpression of lncRNA H19 has been determined to enhance the proliferation, invasion of gastric cancer and contributed to poor prognosis in GC patients in multiple studies 46 - 49 . Naturally, a prognosis-related mRNA-miRNA-lncRNA ceRNA network in gastric cancer was successfully constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive biomarkers for PUD are also under evaluation. In a case‐control study, Mohamed et al examined the use of microRNAs, non‐coding RNAs, and long non‐coding RNAs as biomarkers to detect gastric cancer and its progression from H pylori ‐induced PUD . lncRNA H19, miR‐204, and miR‐182 were identified as potential plasma biomarkers to detect progression to gastric cancer in patients with PUD.…”
Section: Gastric Diseasesmentioning
confidence: 99%